2009
DOI: 10.1128/jcm.00913-09
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Genomic Characterization of Aichi Viruses in Stool Samples from Children in Monastir, Tunisia

Abstract: Aichi virus has been associated with acute gastroenteritis in adults and children. Stool samples were collected from 788 Tunisian children suffering from diarrhea. Aichi virus was found in 4.1% of the cases. The high proportion of monoinfections and the high frequency of hospitalizations support the role of Aichi virus in pediatric gastroenteritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
41
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 15 publications
2
41
2
Order By: Relevance
“…In Tunisia, we previously reported the epidemiology and genomic characterization of AiV strains circulating in the pediatric Tunisian population over more than 4 years (12). In this previous prospective survey, contrary to the data in the literature, we showed that AiV was the third most frequently detected agent, after rotavirus and norovirus, in children with sporadic gastroenteritis symptoms.…”
contrasting
confidence: 51%
See 3 more Smart Citations
“…In Tunisia, we previously reported the epidemiology and genomic characterization of AiV strains circulating in the pediatric Tunisian population over more than 4 years (12). In this previous prospective survey, contrary to the data in the literature, we showed that AiV was the third most frequently detected agent, after rotavirus and norovirus, in children with sporadic gastroenteritis symptoms.…”
contrasting
confidence: 51%
“…In our previous clinical and virological study (12), AiV genomic detection was higher than usually documented: it was found in 32 (4.1% of diarrheic stools) cases, with a high proportion of monoinfection (25; 78.1% of AiV infections) and a high frequency of hospitalizations among the monoinfections (18 versus 7 outpatients; P ϭ 0.04). The 18 children hospitalized presented with gastroenteritis symptoms, especially diarrhea, fever, and vomiting.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The virus was later isolated from patients with gastroenteritis, comprising Pakistani children and Japanese travelers from Southeast Asia (18), and among patients from Japan, Bangladesh, Thailand, and Vietnam (8). In 2006, the virus was isolated for the first time in the Americas (Brazil) and Europe (Germany) (7), and since then, Aichi virus has been detected in France (6), Tunisia (12,13), Hungary (10), and Finland (5).…”
mentioning
confidence: 99%